Correlation between Hormonal Statuses and Metabolic Syndrome in Postmenopausal Women. - Saeideh Ziaei; Hajar Mohseni (Tehran University of Medical Sciences, 2013)
Objective: To compare the hormonal status in postmenopausal women with and without metabolic syndrome. Materials and methods:In this cross sectional study 110 postmenopausal women were enrolled. Participants completed a questionnaire and underwent a medical exam and serum evaluation for serum lipids including cholesterol (Chol), high density lipoprotein cholesterol (HDL), low density lipoprotein (LDL), triglyceride (TG), fasting blood sugar (FBS), sex hormone binding globulin (SHBG), estradiol and testosterone. Metabolic syndrome was defined according to the definition of the National Cholesterol Education Program- Adult Treatment Panel III. In this study P value less than 0.05 was accepted as significant. Results:There were significant differences between the two groups of participants with and without metabolic syndrome in age, years after menopause, BMI, weight, SHBG and testosterone (p< 0.01). Conclusion: SHBG and testosterone are the most significant correlated factors to metabolic syndrome in postmenopausal women.